INCREASING STUDENTS’ VOCABULARY BY USING SONG LYRIC AT THE SECOND GRADE OF SMP NEGERI 3 TOLITOLI - Jaya Jaya (Universitas Madako Tolitoli, 2017)
This research design belongs to a pre-experimental research. This research aims to find out whether the use of song lyric can increasing students’ vocabulary at VIII grade students of SMP Negeri 3 Tolitoli. The instrument of collecting data are pretest and posttest. The test was used obtain data in order to find out the effect of using song lyric. The result of the research shows that: 1. By using song lyric can increasing students vocabulary in listening music, 2. There is significant difference between the result of pretest and posttest , the mean score of posttest was 82.42 it was higher than the mean score of pretest 77.09. 3. The testing hypothesis shows that T-count 9.609 was higher than T table 2.036 it indicates that the null hypothesis (Ho) rejected and (Ha) accepted. That ability was increase after they were taught using song lyric. They was better in their listening music.Key word: Vocabulary, Verb, Lyric, Song, Increase.